Wind-stress misalignment in the presence of swells in the Bay of Bengal - Raj, Abhijith; Kumar, B. Praveen; Jampana, Venkata; Remya, P. G.; Seo, Hyodae; Sureshkumar, N.; Pattabhi Rama Rao, E. (Frontiers in Marine Science, 2025)
This study investigates the directional characteristics of momentum flux, τ, under diverse wind-wave conditions in the Bay of Bengal (BoB). Using high-frequency data from an eddy covariance flux system deployed on a moored buoy, we identify various cases of wind-swell alignment and their resulting τ directions, with emphasis on seasonal variations. During June-August (JJA), when winds and swells are generally aligned, τ lies between wind and swell directions in 34% of wind-dominated cases, facilitating momentum transfer to developing seas. However, in 57% of cases where swells dominate or winds weaken, τ shifts toward the swell direction. In December-February (DJF), counter-swell conditions with moderate winds dominate, aligning τ between wind and opposing swell directions under wind dominance or between wind and swell directions when swells dominate. For the first time, this study quantifies the biases in Monin-Obukhov Similarity Theory (MOST)-based bulk flux models, which underestimate stress by ~12% under counter-swell conditions and ~7% in swell-dominated regimes due to their inability to account accurately the sea-state effects. These findings highlight the key role of wind-swell misalignment and swell-induced stresses in modulating τ direction and magnitude. Our results emphasize the need for parameterizations that account more accurately the sea-state effects to improve air-sea interaction models in seasonally wind-reversing, swell-dominated regions like the BoB.